Artificial Intelligence in Digital Marketing Performance Optimization for Micro Small and Medium Enterprises in Surakarta - Ribhi, Ahmad Aufar; Budiono, Graceilla Kristia Seraphim; Rizki, Muhammad Ircham (SAFE-Network, 2025)
Digital marketing has become a necessity for Micro, Small, and Medium Enterprises (MSMEs) to increase their competitiveness in the digital economy era. Artificial Intelligence (AI) plays a central role in this revolution, particularly in the field of digital marketing, by reducing targeting complexity, enabling predictive analytics, and personalizing content, which is crucial for businesses with limited resources like MSMEs. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation, selecting Surakarta MSME respondents who had never used AI in their digital marketing. This study focuses on proving the effectiveness of using AI, which is currently a trend, in improving MSME digital marketing performance. The results of the testing documentation comparing Meta Advantage+ (AI-based) with a prospecting set up or structured control (without AI) showed a good improvement in digital marketing performance. The use of AI in digital marketing was proven to provide a substantial increase in key ad campaign performance parameters such as Click Through Rate and Conversion Rate. This optimization occurred thanks to AI's ability to analyze consumer behaviour, perform hyper-personalization targeting, and automate effective ad allocation. generally, AI assists MSMEs in product and market research, formulating marketing strategies, and increasing operational efficiency. Although AI offers great opportunities to optimize MSME performance, its implementation in Surakarta still faces a number of multidimensional challenges. The main obstacles include low technological literacy and a lack of human resources with expertise in technology within the MSME sector. Furthermore, ethical issues, such as privacy risks and the security of sensitive data in AI systems, are also concerns for business owners when creating ad campaigns. The implementation of AI through Meta Advantage+ is proven to increase efficiency, service personalization, and digital promotion effectiveness. To maximize AI potential and achieve competitive advantage, MSMEs are advised to adopt a strategic approach that prioritizes collaboration between AI and humans, accompanied by increased digital literacy and human oversight to overcome ethical and technical obstacles.